2009
DOI: 10.1098/rspb.2009.1174
|View full text |Cite
|
Sign up to set email alerts
|

Competition promotes the evolution of host generalists in obligate parasites

Abstract: Ecological theory traditionally predicts that interspecific competition selects for an increase in ecological specialization. Specialization, in turn, is often thought to be an evolutionary 'dead end,' with specialist lineages unlikely to evolve into generalist lineages. In host-parasite systems, this specialization can take the form of host specificity, with more specialized parasites using fewer hosts. We tested the hypothesis that specialists are evolutionarily more derived, and whether competition favours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 39 publications
1
63
0
Order By: Relevance
“…1), we found that all gains of host generalists occurred in louse lineages found on doves that spend most of their time on the ground (concentrated changes test P = 0·037 over Bayesian tree, P = 0·022 over parsimony tree). There was no such correlation (P = 0·26) for wing lice when we repeated the analysis using data from Johnson et al (2009).…”
Section: Comparative Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…1), we found that all gains of host generalists occurred in louse lineages found on doves that spend most of their time on the ground (concentrated changes test P = 0·037 over Bayesian tree, P = 0·022 over parsimony tree). There was no such correlation (P = 0·26) for wing lice when we repeated the analysis using data from Johnson et al (2009).…”
Section: Comparative Resultsmentioning
confidence: 94%
“…In contrast, host specialists do not disperse and/or establish on more than one host species. We coded the presence of a potentially competing species following Johnson et al (2009), using host association records from Price et al (2003) and additional associations represented in the published molecular data set (Johnson et al 2011).…”
Section: Comparative Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other hundreds of helminth species that infect humans also infect other host species. Most recently, Johnson et al (2009) presented phylogenetic and experimental support of the hypothesis that host specificity is an ancestral condition. Generalists evolved from specialist ancestors.…”
Section: A Synthesis Of Parasitology and Archaeoparasitologymentioning
confidence: 97%
“…For example, host specificity of phage ⌽ -6 depends largely on receptor recognition, and the virus seems unable to produce a protein that can recognize multiple bacterial receptors simultaneously, so adaptation to new hosts usually results in loss of recognition of the old host receptor [Ferris et al, 2007]. Some environmental conditions may have an effect on the selection of specialists or generalists, such as interspecies competition [Johnson et al, 2009], coevolution with the host [Hall et al, 2011], or the supply of beneficial variation [Jasmin and Kassen, 2007], which does not seem to be limiting in RNA viruses [Betancourt, 2009;Bollback and Huelsenbeck, 2007;Dutta et al, 2008]. While there are some arguments as to whether true generalists exist in nature [Loxdale et al, 2011], arboviruses are usually considered the ultimate generalists due to their potential to replicate and perform well in a wide variety of hosts [Weaver, 2006].…”
Section: Selection For Generalization and Specializationmentioning
confidence: 99%